Use of medicinal plants for the treatment of urinary Tract infections: a study from paschim Medinipur district, West bengal, India - SUDESHNA PATTANAYAK,; DULAL CHANDRA DAS,; NIRMALYA KUMAR SINHA,; SHWETA PARIDA, (International Journal of Pharma and Bio Sciences, 2017)
Urinary tract infections (UTIs) have become a severe public health problem affecting millions of people worldwide. These are caused by a range of pathogens, where Candida albicans, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus saprophyticus most common. High recurrence rates and increasing antimicrobial resistance among uropathogens make the situation more serious. The traditional medicines are the best alternatives to control the UTIs, as these medicines are used from the time of immemorial with same efficacy. Up till now a little attention has been paid on documentation of medicinal plants used for the treatment of UTIs from Paschim Medinipur district. An attempt has been made to collect the information about the use of phytomedicine for the treatment of UTIs of Paschim Medinipur district. The prescription of ethnomedicine were thoroughly interviewed and cross interviewed with the local healers, patients, old and experienced local peoples regarding doses and administration. About fifty three indigenous medicinal plants under thirty five families have been recorded. The present investigation is an important thrust area to the society for the treatment of UTIs and also helpful for the detailed account of the studied medicinal plant for future research to generate new phytochemicals and to formulate new bioactive compounds in the medical world.